Peran Musik dalam Ibadah Kristen: Tinjauan Sitematis Terhadap Dimensi Liturgis dan Spritualitas (Systematic Literature Review) - Jumaroh, Ita (Innovative: Journal Of Social Science Research, 2025)
Music plays a central role in Christian worship, not only as an aesthetic element but also as an important means to deepen the liturgical and spiritual dimensions of the congregation. The background of this study highlights how music facilitates the relationship between the congregation and God, creates a reflective and worshipful atmosphere, and functions theologically to strengthen faith and communal bonds. The purpose of this study is to systematically review the role of music in Christian worship, particularly in the liturgical and spiritual dimensions. The research method used is a Systematic Literature Review (SLR) by identifying, evaluating, and synthesizing relevant previous research. The literature search process was carried out through academic databases such as Google Scholar and DOAJ with keywords such as "music in Christian worship," "liturgical music," "Christian spirituality," and "the role of music in the liturgy." Inclusion criteria included English and Indonesian language scientific articles published between 2013 and 2023 and explicitly discussing the relationship between music, liturgy, and spirituality in the context of Christian worship. The research findings indicate that music in Christian worship serves to strengthen the structure and meaning of each section of the service, convey theological messages through meaningful lyrics, and set the emotional rhythm of the service. Furthermore, music has a unique ability to engage the emotional, reflective, and contemplative dimensions of the congregation, thereby strengthening their spirituality. Music also serves as a means of catharsis, deepening theological reflection, and building communal solidarity. The typology of Christian worship music can be classified as traditional, contemporary, and charismatic, each with distinct characteristics and functions according to the denominational context and the needs of the congregation.